Voices of the old sea - Lewis, Norman (Eland, 2013)
Describes the Costa Brava, a place where men regulated their lives by the sardine shoals of spring and autumn and the tuna fishing of summer, and where women kept goats and gardens, arranged marriages and made ends meet.